Panpsychism, conceivability, and dualism redux - Htut Maung, Hane (Array, 2019)
In contemporary philosophy of mind, the conceivability argument against physicalism is often used to support a form of dualism, which takes consciousness to be ontologically fundamental and distinct from physical matter. Recently, some proponents of the conceivability argument have also shown interest in panpsychism, which is the view that mentality is ubiquitous in the natural world. This paper examines the extent to which panpsychism can be sustained if the conceivability argument is taken seriously. I argue that panpsychism’s ubiquity claim permits a strong reading or a weak reading. This presents a dilemma. On the one hand, the strong reading, which is typically characterised as a form of monism, is undermined by the conceivability argument. On the other hand, the weak reading, while compatible with the conceivability argument, turns out just to be a special case of dualism. I also show that the related position of panprotopsychism cannot provide a tenable monist position because it too cannot withstand the challenge of the conceivability argument. Therefore, if the conceivability argument is taken seriously, then we are committed to a dualist metaphysics, regardless of whether or not we accept the ubiquity claim.